Disclosing complex mutational dynamics at a Y chromosome palindrome evolving through intra- and inter-chromosomal gene conversion. Issue 1 (3rd August 2022) - Bonito, Maria; Ravasini, Francesco; Novelletto, Andrea; D'Atanasio, Eugenia; Cruciani, Fulvio; Trombetta, Beniamino
Abstract: The human MSY ampliconic region is mainly composed of large duplicated sequences that are organized in eight palindromes (termed P1–P8), and may undergo arm-to-arm gene conversion. Although the importance of these elements is widely recognized, their evolutionary dynamics are still nuanced. Here, we focused on the P8 palindrome, which shows a complex evolutionary history, being involved in intra- and inter-chromosomal gene conversion. To disclose its evolutionary complexity, we performed a high-depth (50×) targeted next-generation sequencing of this element in 157 subjects belonging to the most divergent lineages of the Y chromosome tree. We found a total of 72 polymorphic paralogous sequence variants that have been exploited to identify 41 Y-Y gene conversion events that occurred during recent human history. Through our analysis, we were able to categorize P8 arms into three portions, whose molecular diversity was modelled by different evolutionary forces. Notably, the outer region of the palindrome is not involved in any gene conversion event and evolves exclusively through the action of mutational pressure. The inner region is affected by Y-Y gene conversion occurring at a rate of 1.52 × 10 −5 conversions/base/year, with no bias towards the retention of the ancestral state of the sequence. In this portion, GC-biased gene conversion is counterbalanced by a mutational bias towards AT bases. Finally, the middle region of the arms, in addition to intra-chromosomal gene conversion, is involved in X-to-Y gene conversion (at a rate of 6.013 × 10 −8 conversions/base/year) thus being a major force in the evolution of the VCY/VCX gene family.